2018
DOI: 10.1002/adma.201707093
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Spectrally Stable Red Perovskite Light‐Emitting Diodes

Abstract: Perovskite light-emitting diodes (LEDs) have recently attracted great research interest for their narrow emissions and solution processability. Remarkable progress has been achieved in green perovskite LEDs in recent years, but not blue or red ones. Here, highly efficient and spectrally stable red perovskite LEDs with quasi-2D perovskite/poly(ethylene oxide) (PEO) composite thin films as the light-emitting layer are reported. By controlling the molar ratios of organic salt (benzylammonium iodide) to inorganic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
183
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(189 citation statements)
references
References 49 publications
6
183
0
Order By: Relevance
“…Both devices were driven under a constant current density of 10 mA cm −2 . Tian et al has reported one of the most stable red quasi-2D perovskite LED with the EL intensity remained almost unchanged for 4 h due to a decrease in ion migration from the quasi-2D structure [112].…”
Section: Quasi-2d Perovskitementioning
confidence: 99%
See 1 more Smart Citation
“…Both devices were driven under a constant current density of 10 mA cm −2 . Tian et al has reported one of the most stable red quasi-2D perovskite LED with the EL intensity remained almost unchanged for 4 h due to a decrease in ion migration from the quasi-2D structure [112].…”
Section: Quasi-2d Perovskitementioning
confidence: 99%
“…Therefore, the defects such as undercoordinated Pb at the surface can be passivated by Lewis bases [114]. In the literature, Lewis bases such as amine (-NH 2 ) [81], hydroxyl (-OH) [47,112,115], carboxyl (-COOH) [29] and phosphine oxide (P=O) [21,47] derivatives are widely used as passivation agents for perovskites. More recently, except for the essential passivating functional groups, it was found that the hydrogen-bonding ability between the passivation agents and the organic cations in perovskites also played an important role on the effectiveness of passivation.…”
Section: Suppressing Grain Boundary Ion Migrationmentioning
confidence: 99%
“…Lowering the dimensionality to 2D with corner‐sharing octahedral layers and bulky organic cations separating perovskite layers gives rise to increased structural diversity and new functionalities . Besides, 2D hybrid perovskites have attracted much attention as alternative photovoltaic materials because of an improved stability arising from hydrophobic interactions, which block moisture diffusion in the material . In 2D perovskites, there is no Goldschmidt's tolerance factor restriction .…”
Section: Figurementioning
confidence: 99%
“…[9][10][11] Besides,2 Dh ybrid perovskites have attracted much attention as alternative photovoltaic materials because of an improved stability arising from hydrophobic interactions,w hich block moisture diffusion in the material. [12][13][14] In 2D perovskites,t here is no Goldschmidtstolerance factor restriction. [15] As aresult, the optical and electronic properties of the materials can be tuned not only by metal cation and halide anion but also organic molecules with different sizes and functional groups,p roviding almost unlimited compositional and structural versatility.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] Even though other optoelectronic devices like light emitting diodes and lasers are being researched, [6][7][8][9][10][11][12][13] perovskite-based photovoltaics (PV) is the key technology driving the fast emergence of perovskitebased optoelectronics. [1][2][3][4][5] Even though other optoelectronic devices like light emitting diodes and lasers are being researched, [6][7][8][9][10][11][12][13] perovskite-based photovoltaics (PV) is the key technology driving the fast emergence of perovskitebased optoelectronics.…”
mentioning
confidence: 99%